Academic Procrastination and Its Relationship to Psychological and Social Adjustment among University Students - Abood, Mohammad; Al-Adamat, Omar (Islamic Guidance and Counseling Journal, 2025)
This study sought to identify the levels of academic procrastination and psychological and social adjustment among Hashemite University students and to reveal whether there are any differences in the psychological and social adjustment attributable to the variables of gender, college, and academic level. Moreover, the study examined the correlation between academic procrastination and psychological and social adjustment. The study recruited (350) students from Hashemite University. The Academic Procrastination and the Psychological and Social Adjustment scales were utilised to achieve the objectives. The findings showed that (65.1%) of the students had a medium level of academic procrastination, and (4.6%) of the students had substantial levels and a moderate level of psychological and social adjustment. The results demonstrated that the gender variable contributed to statistically significant differences in the degree of psychological and social adjustment. Finally, academic procrastination and psychological and social adjustments were found to be negatively and statistically significantly correlated. The study recommends providing support to university students, by helping them identify the challenges they face, find solutions for them, and overcome them with the aim of achieving their ambitions, in a way that enhances their psychological and social adjustment.